Pirfenidone Accelerates Wound Healing in Chronic Diabetic Foot Ulcers: A Randomized, Double-Blind Controlled Trial - Luz E. Gasca-Lozano; Silvia Lucano-Landeros; Héctor Ruiz-Mercado; Adriana Salazar-Montes; Ana Sandoval-Rodríguez; Jesus Garcia-Bañuelos; Arturo Santos-Garcia; Judith R. Davila-Rodriguez; José Navarro-Partida; Hiram Bojórquez-Sepúlveda; Juan Castañeda-Gomez; José Domínguez-Rosales; et al. (Journal of Diabetes Research)
Background. Diabetic foot ulcers are one disabling complication of diabetes mellitus. Pirfenidone (PFD) is a potent modulator of extracellular matrix. Modified diallyl disulfide oxide (M-DDO) is an antimicrobial and antiseptic agent. Aim. To evaluate efficacy of topical PFD + M-DDO in a randomized, double-blind trial versus ketanserin in the treatment of noninfected chronic DFU. Methods. Patients received PFD + M-DDO or ketanserin for 6 months. Relative ulcer volume (RUV) was measured every month; biopsies were taken at baseline and months 1 and 2 for histopathology and gene expression analysis for COL-1α, COL-4, KGF, VEGF, ACTA2 (α-SMA), elastin, fibronectin, TGF-β1, TGF-β3, HIF-1α, and HIF-1β. Results. Reduction of median RUV in the PFD + M-DDO group was 62%, 89.8%, and 99.7% at months 1–3 and 100% from months 4 to 6. Ketanserin reduced RUV in 38.4%, 56%, 60.8%, 94%, 94.8%, and 100% from the first to the sixth month, respectively. Healing score improved 4.5 points with PFD + M-DDO and 1.5 points with ketanserin compared to basal value. Histology analysis revealed few inflammatory cells and organized/ordered collagen fiber bundles in PFD + M-DDO. Expression of most genes was increased with PFD + M-DDO; 43.8% of ulcers were resolved using PFD + M-DDO and 23.5% with ketanserin. Conclusion. PFD + M-DDO was more effective than ketanserin in RUV reduction.